Hermeneutics of the Pattern of Personal Knowledge in the Caring Function of the Nursing Role, Chile, 1976 [Hermenéutica del Patrón de Conocimiento Personal en la Función Asistencial del Rol de Enfermería, Chile, 1976 - Castillo-Lobos, L; Nunez-Carrasco, E (Escuela de Enfermeria Pontificia Universidad Catolica de Chile, 2025)
INTRODUCTION. Carper s pattern of personal nursing knowledge has been considered an essential part of nursing work, specifically in nurse-patient interaction. The manifestation of this pattern of knowledge has never been analyzed in the history of Chilean nursing in the 1970s, a period in which nursing managed to adapt and continue its work, despite the setbacks in its power due to the socio-political context. OBJECTIVE. To analyze the manifestation of Carper s Personal Knowledge pattern in the caring function of the Chilean nurse s role in 1976. METHOD. Exegetical study, hermeneutic analysis of Carper s philosophy, and the caring function in the Role of the Nurse (1976), according to Schleiermacher s and Dilthey s hermeneutics, through three selected texts. RESULTS AND DISCUSSION. This study analyzes how the personal knowledge pattern manifests in the caring function from a hermeneutic perspective, considering the historical context of the time and its influence. It addresses personal and contextual questions in the comprehension process. CONCLUSIONS. The Role of the Nurse (1976), as a manifestation of life, is a statement of the functions and expression of a historical power achieved. The personal knowledge pattern emerges as essential for the therapeutic use of self, yet it demands effort in the comprehension process, posing a hermeneutic challenge. This approach advances the ontology of nursing, which plays a key role in the nurse-patient relationship. © 2025, Escuela de Enfermeria Pontificia Universidad Catolica de Chile. All rights reserved.